Police Consolidation in the News. (June 2014) - Chermak, Steven; Scheer, Charles; Wilson, Jeremy M.
Although there is a large body of research on media coverage of crime and criminal justice issues, there is significantly less information about policing issues generally, and there has not been a study that specifically examines how the consolidation of law enforcement agencies has been presented in the news. This study fills this gap. We explore two general themes. First, we detail what issues about consolidation have been emphasized in the news. Second, we examine the types of sources that news reporters have relied on and how they have used them in stories about consolidation.